Influence of Personal, Psychological and Institutional Factors on Academic Performance of Students of Veterinary Science and Animal Husbandry - S, Suganya; M, Thirunavukkarasu; A, Serma Saravana Pandian; C, Balan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted to explore and identify the personal and psychological characteristics towards study and institutional factors that influence the academic performance of students of veterinary science and animal husbandry from the data gathered through personal interview using structured pre-tested interview schedule from 280 students of TANUVAS selected using stratified random sampling procedure. Analysis of the data collected using χ test revealed that there were significant (P < 0.05) associations between the time spent on studies after class hours, parental observation on studies, students’ interest in pursuing higher studies, having personal textbooks and college of study, each with the academic performances of students of veterinary science and animal husbandry. Further, there was a highly significant (P < 0.01) association between the difficulty experienced in understanding topics and poor academic performance of the students. However, there was no significant (P > 0.05) association between the pressure of curriculum and students’ perceptions on institutional facilities on academic performance